Argumentative Knowledge Construction Process in Social Collaborative Learning Environment towards Students' Higher Order Thinking Skills. - Ibrahim, Siti Nur Khadijah Aishah; Harun, Jamalludin (Pertanika Journal of Social Sciences & Humanities)
Nowadays, "thinking about thinking" skills is essential in 21 century education. Preliminary studies demonstrated that students' thinking skills will produce significant results when it is done in collaboration with colleagues. Working in a collaborative environment typically involves processes of evidence and argumentation. Argumentation refers to a claim supported by convincing evidence of extensive and comprehensive understanding of various aspects of an issue. In social collaborative argumentation, knowledge is constructed and shared among peers and the property of a single individual. The challenge is to ensure that argumentative knowledge construction process in social collaborative learning environment improves students' thinking skills. The aim of this paper is to analyze the process involved in argumentative knowledge construction and identifying the process in social collaborative learning environment that contributes towards higher order thinking skills among students. Seventeen students from the Computer Science program participated in the study were randomly divided into 3 groups of four and 1 group of five. This study used mixed method research design concerning the pre-experimental research design that involved type one-group pre-test and post-test design. Data was obtained from performance test and log data files from the social collaborative learning environment. Results showed that argumentative knowledge construction process in social collaborative learning environment could lead students towards higher order thinking skills.